Gambaran Infestasi Vektor pada Kapal Penumpang dan Kapal Barang yang Sandar di Pelabuhan Baubau - Adi Supryatno; Sischa Andriani Alimin (JOURNAL OF BAJA HEALTH SCIENCE, 2022)
ABSTRACT High transportation needs can cause health problems, such as vector infestation. Vector infestation is most likely caused by the behavior of the crew, the age of the ship, the number of passengers, the cleanliness of the ship, and resistance to continuous use of pesticides. The purpose of this study was to describe the location of vector infestations on passenger ships and cargo ships that dock at Baubau port. This type of research is a quantitative descriptive using a cross sectional study design. The object of this research is the ships that docked at the Bau-bau port in December 2017 as many as 12 passenger ships and 12 cargo ships. Insect prevalence was measured by calculating the percentage of the number of insects caught. The results of the research were processed descriptively to see a description of the location of vector infestations on passenger ships and cargo ships that docked at Bau-bau Harbor by looking at the characteristics of the ship based on the type of ship and the age of the ship. The results obtained that cockroaches are the vectors with the highest infestation on ships as many as 10 on passenger ships and 11 on cargo ships. The average age of ships that dock at Baubau port is quite old. Vessels > 7 years old have the most vector infestations and cockroaches are one of the most numerous types of vectors. Keywords: Vector Infestation, Passenger Ship, Freight Ship